1992
DOI: 10.1103/physrevb.46.4630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the parabolic potential and confined phonons on the polaron in a quantum wire

Abstract: By using the Lee, Low, and Pines variational method, we have studied the electron-confined phonon interaction within a rectangular quantum wire under an additional parabolic potential. Formulas for the polaron self-energy, the electron effective mass along the wire, and the ground-state energy are derived. Numerical calculations are performed for a typical GaAs quantum wire within the mesoscopic size using the idea of Fourier decomposition of the wave function. In comparison with previous calculations, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…The evidence for the existence of a parabolic potential well in a quantum wire is reported by Kash [2]. The effects of the parabolic potential have been investigated in several papers [28][29][30][31][32][33][34][35][36]. To our knowledge, there has been no report of the effect of the parabolic potential on the ground-state binding energy of an off-center donor in a spherical quantum dot.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for the existence of a parabolic potential well in a quantum wire is reported by Kash [2]. The effects of the parabolic potential have been investigated in several papers [28][29][30][31][32][33][34][35][36]. To our knowledge, there has been no report of the effect of the parabolic potential on the ground-state binding energy of an off-center donor in a spherical quantum dot.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from that for case absent a magnetic field (index of the landau level that electrons can reach after the absorption process is arbitrary), therefore, the dependence of the absorption coefficient α on Ω  is not continuous. I  can be written from (Li et al, 1992):…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The magnetic field produces not only a parabolic scalar potential for the electron motion but also a interaction between the orbital angular momentum and the magnetic field. Therefore it can be obviously found that the vector potential introduced here has a distinct influence on the electron motion compared with that of the scalar potential used in [4]. Our object is to study the novel result caused by the magnetic field.…”
Section: Theorymentioning
confidence: 96%